1994
DOI: 10.1038/bjc.1994.385
|View full text |Cite
|
Sign up to set email alerts
|

5-fluorouracil and folinic acid-induced mucositis: no effect of oral glutamine supplementation

Abstract: In some clinical situations the endogenous production of glutamine may be insufficient to maintain optimal tissue structure and function such that glutamine becomes a conditionally essential amino acid. Studies in laboratory animals have demonstrated that glutamine supplementation can reduce the incidence and severity of cytotoxic-induced mucositis. This study examined the role of oral glutamine supplementation in the management of mucositis caused by 5-fluorouracil (5-FU) and folinic acid. Twenty-eight patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
5

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 11 publications
2
77
0
5
Order By: Relevance
“…Different observations regarding the efficacy of oral glutamine 15,28 for amelioration of chemotherapy-associated mucositis could be related to different glutamine concentrations in the oral mucosa, as well as the route and schedule of administration. Because of poor solubility and biodistribution, only a suspension can achieve a high local concentration in the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different observations regarding the efficacy of oral glutamine 15,28 for amelioration of chemotherapy-associated mucositis could be related to different glutamine concentrations in the oral mucosa, as well as the route and schedule of administration. Because of poor solubility and biodistribution, only a suspension can achieve a high local concentration in the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Because of poor solubility and biodistribution, only a suspension can achieve a high local concentration in the oropharynx. If glutamine is either dissolved 28 or given intravenously, 21,29 the concentration in the oral mucosa may be insufficient to significantly ameliorate mucositis and its associated pain.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel ulceration caused by these anti-metabolites and corresponding bacteraemia was reduced (Fox et al, 1988). However, when additional glutamine supplements were given to patients suffering from gastrointestinal cancer, treated by 5-fluorouracil and folinic acid in a placebo-controlled double-blind trial, there was no difference in the degree of observed oral mucositis (Jebb et al, 1994).…”
Section: Anti-ulcer Agentsmentioning
confidence: 99%
“…There is also a reduction in infections with intravenous glutamine. There is, however, an increase in relapse with intravenous Objective Cerchietti et al (12) Daniele et al (13) Huang et al (15) Jebb et al (16) Okuno et al (17) Peterson et al (18) Subtotal (95 % CI) Total events Heterogeneity: 蠂 2 5.24, df 4 (P=0路26); I 2 24 % Test for overall effect: Z 1路07 (P=0路28) Subjective Huang et al (15) Okuno et al (17) Subtotal (95 % CI) Total events Heterogeneity: 蠂 2 0路00, df 1 (P=1路00); I 2 0 % Test for overall effect: Z 0路45 (P=0路65) Objective Huang et al (15) Jebb et al (16) Okuno et al (17) Peterson et al (18) Subtotal ( glutamine but this result was based on two small studies (30,32) of patients undergoing autologous transplantation.…”
Section: Bone-marrow Transplantationmentioning
confidence: 99%